Pengendalian Risiko pada Pekerjaan Block Assembly Proyek Barge Mounted Power Plant Menggunakan Job Hazard Analysis - Adika Pratama; Restu Hikmah Ayu Murti (Yayasan Literasi Sains Indonesia, 2023)
A Barge Mounted Power Plant (BMPP) is a floating power generation technology based on a ship that converts solar fuel and dual fuel gas into electrical energy. The manufacturing process involves assembling separate parts and combining them into larger sections, which increases the risk of workplace accidents. According to data from the BPJS Employment Accident Insurance program in 2021, there were 234,270 workplace accidents. The purpose of this study is to (1) identify potential hazards and risks that may occur and (2) control the risks associated with each process activity to ensure that the work is performed safely. The research method used is a qualitative descriptive approach based on risk analysis using job hazard analysis. The results of this study identified five types of hazards: psychological, mechanical, physical, ergonomic, and environmental. In conclusion, this study identified 13 process activities and 39 potential hazards and risks, and proposed measures to control the risks.